Preparation process of high-performance graphite negative electrode material
By porousizing graphite negative electrode materials, in-situ synthesis of tin dioxide and COF coating treatment, the problem of insufficient performance of traditional graphite negative electrode materials is solved, and the cycle stability, rate performance and safety performance are significantly improved. It is suitable for high-performance lithium Battery application.
Patent Information
- Application Number
- CN202411657540.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional graphite anode materials cannot meet the growing demand for high-performance electrical appliances, especially in improving the rate performance, cycle stability and safety performance of the anode materials.
Porous graphite is formed by mixing natural graphite with ammonium sulfate and treating it at high temperature, and then tin dioxide is synthesized in situ between its surface and layers, followed by coating the covalent metal organic frame (COF) material and secondary coating To improve structural stability, high-performance graphite negative electrode material was prepared.
It significantly improves the cyclic stability, rate performance, safety performance and specific capacity of the negative electrode material, enhances the electrochemical reaction active site, slows down the volume expansion during the charging and discharging process, improves the first Coulomb efficiency and cycling performance, and enhances the Low temperature performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery negative electrode materials, and in particular to a preparation process of a high-performance graphite negative electrode material. Background Art
[0002] Lithium-ion batteries have the advantages of light weight, high energy density, long cycle life, high operating voltage, no memory effect, and no environmental pollution. They have been widely used in portable electronic devices such as mobile phones, laptops, and cameras. With the continuous research and development of lithium-ion batteries, their application has gradually extended to the fields of hybrid vehicles and electric vehicles, and has become one of the most promising energy storage devices.
[0003] As one of the key components of lithium-ion batteries, the negative electrode material determines the performance of the battery. At present, the negative electrode materials of lithium-ion batteries mainly include silicon negative electrode materials, carbon negative electrode materials, tin negative electrode materials and lithium titanate negative electrode materials. Graphite negative electrode materials are widely used in lithium batteries due to their excellent specific capacity, low cost and good cycle performance. However, traditional graphite negative electrodes can no longer meet the growing demand for high-performance electrical appliances. Therefore, it is necessary to modify the graphite negative electrode by surface coating, chemical modification, element doping and other modification treatments to further improve the rate performance, cycle stability and other properties of the negative electrode material. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a process for preparing a high-performance graphite negative electrode material.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A high-performance graphite negative electrode material preparation process, specifically prepared by the following steps: Step S1, mixing and grinding natural graphite and ammonium sulfate, transferring the ground product into a quartz crucible, heat treating it under nitrogen and high temperature conditions for 3-4 hours, and cooling it to room temperature to obtain porous graphite; Step S2, mixing tin tetrachloride in ethanol and stirring evenly, adding porous graphite to ultrasonicate, stirring, centrifuging, washing, freeze-drying, and then calcining at high temperature to obtain a PNG / SnO2 composite material; Step S3, ultrasonically dispersing the PNG / SnO2 composite material in acetonitrile for 10-20 minutes, adding melamine and stirring for 0.5-1.5 hours, then adding terephthalaldehyde and acetic acid solution, continuously stirring for 18-24 hours, standing for 1-3 hours, centrifuging, washing, and drying to obtain the PNG / SnO2@COF composite material; Step S4, stirring the PNG / SnO2@COF composite material and the tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer in boiling deionized water for 30 minutes, then transferring to an autoclave for reaction for 8-12 hours, centrifuging and drying, and then sintering in a tubular furnace to obtain a graphite negative electrode material; Further, the temperature during the heat treatment in step S1 is 1200-1400°C; Further, in step S1, the mass ratio of natural graphite to ammonium sulfate is 5-10:0.03-0.1; Further, in step S2, the usage ratio of tin tetrachloride, ethanol, and porous graphite is 0.5-3 g: 50 mL: 0.05-0.2 g; Further, in step S2, after the porous graphite is added, the ultrasonic treatment time is 3-5h; the stirring speed is 500-700rpm / min, and the time is 15-20h; Furthermore, the high temperature calcination in step S2 is performed at a temperature of 700-900°C and a time of 1.5-3.5h; Further, in step S3, the usage ratio of PNG / SnO2 composite material, acetonitrile, melamine, terephthalaldehyde and acetic acid solution is 1 g: 100 mL: 0.02-0.03 mol: 0.05-0.07 mol: 0.2-0.5 mL; Further, the concentration of the acetic acid solution in step S3 is 3-6 mol / L; Further, in step S4, the mass ratio of the PNG / SnO2@COF composite material, the tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer and the deionized water is 3-5:0.03-0.09:60; Furthermore, in step S4, the reaction temperature in the autoclave is 160-180° C., the sintering temperature in the tubular furnace is 280-310° C., and the sintering time is 4.5-5.5 h.
[0006] Beneficial effects of the present invention: The high-performance graphite negative electrode material of the present invention uses natural graphite with good conductivity, high specific capacity, low cost and good cycle stability as a base material, and pre-treats the natural graphite to obtain porous graphite, then uses tin tetrachloride as a raw material, in-situ synthesizes tin dioxide on the surface and between layers of the porous graphite to obtain a PNG / SnO2 composite material, and then coats a covalent metal organic framework to obtain a PNG / SnO2@COF composite material, and finally uses tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer as a carbon material to achieve secondary coating to obtain a graphite negative electrode material, thereby improving the cycle stability, rate performance, safety performance and specific capacity of the negative electrode material; therefore, the application of the negative electrode material in lithium batteries has a good application prospect.
[0007] In the PNG / SnO2@COF composite material, natural graphite is first processed, blended and ground with ammonium sulfate, and then treated at high temperature to obtain porous graphite; then, using porous graphite as a substrate and tin tetrachloride as a raw material, tin dioxide is in situ synthesized on the surface and between layers of the porous graphite to obtain the PNG / SnO2 composite material; then, using melamine and terephthalaldehyde as raw materials, COF is coated on the surface of the PNG / SnO2 composite material to obtain the PNG / SnO2@COF composite material.
[0008] The graphite negative electrode material of the present invention utilizes the synergistic effect between graphite, tin dioxide and CO to comprehensively improve the cycle stability, rate performance, safety performance and specific capacity of the negative electrode material; wherein ammonium sulfate is introduced into the surface and interlayer of natural graphite after being blended and ground, and then the corrosive gas generated by the thermal decomposition of ammonium sulfate is used to corrode the surface and interior of the graphite, thereby forming a rich pore structure and increasing the specific surface area, thereby shortening the Li + The diffusion path increases the electrochemical reaction active sites, thereby improving the rate performance of the negative electrode material. At the same time, the rich pore structure can also alleviate the Li + The huge volume change during the deintercalation process improves the cycle stability and safety of the negative electrode material; the synergistic effect of tin dioxide and graphite can make up for the low specific capacity caused by graphite alone as the negative electrode material, and improve the specific capacity of the matrix; the close combination of COF material and PNG / SnO2 composite material slows down the Li + The volume expansion caused by the continuous insertion and removal, and the existence of the coating layer, prevents the direct contact between the PNG / SnO2 composite material and the electrolyte, reduces the formation of the SEI film during the cycle, and effectively improves the initial coulombic efficiency, cycle performance and rate performance of the negative electrode material. At the same time, COF has abundant porous channels, cavity structures and gaps, which can accelerate the Li + In addition, the use of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer as a carbon material for secondary coating can inhibit the co-embedding of solvent molecules and the exfoliation of graphite sheets, enhance the structural stability of the negative electrode material, electronic conduction and Li + The migration in the negative electrode material and the doping of F on the surface also improve the low-temperature performance of the negative electrode material. DETAILED DESCRIPTION
[0009] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0010] The graphite negative electrode material composite material is prepared by the following steps: Step S1, 5 g of natural graphite and 0.03 g of ammonium sulfate are mixed and ground, and the ground product is transferred to a quartz crucible, heat treated for 3 h under nitrogen at 1200° C., and cooled to room temperature to obtain porous graphite; Step S2, 0.5 g of tin tetrachloride was mixed and stirred in 50 mL of ethanol, 0.05 g of porous graphite was added, ultrasonicated for 3 h, stirred at a speed of 500 rpm for 15 h, centrifuged, washed, freeze-dried, and then calcined at 700 ° C for 1.5 h to obtain a PNG / SnO2 composite material; Step S3, ultrasonically disperse 1 g of PNG / SnO2 composite material in 100 mL of acetonitrile for 10 min, add 0.02 mol of melamine and stir for 0.5 h, then add 0.05 mol of terephthalaldehyde and 0.2 mL of 6 mol / L acetic acid solution, continue stirring for 18 h, let stand for 1 h, centrifuge, wash, and dry to obtain a PNG / SnO2@COF composite material; Step S4, stirring 3g of PNG / SnO2@COF composite material and 0.03g of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer in 60g of boiling deionized water for 30min, then transferring to an autoclave to react at 160°C for 8h, centrifuging and drying, and then placing in a tubular furnace and sintering at 280°C for 4.5h to obtain a graphite negative electrode material. Example 2
[0011] The graphite negative electrode material is prepared by the following steps: Step S1, 7 g of natural graphite and 0.05 g of ammonium sulfate were mixed and ground, and the ground product was transferred to a quartz crucible, heat treated for 3.5 h under nitrogen at 1300° C., and cooled to room temperature to obtain porous graphite; Step S2, 1 g of tin tetrachloride was mixed and stirred in 50 mL of ethanol, 0.1 g of porous graphite was added, ultrasonicated for 4 h, stirred at a speed of 600 rpm for 17 h, centrifuged, washed, freeze-dried, and then calcined at 800 ° C for 2.5 h to obtain a PNG / SnO2 composite material; Step S3, ultrasonically disperse 1 g of PNG / SnO2 composite material in 100 mL of acetonitrile for 15 min, add 0.024 mol of melamine and stir for 1 h, then add 0.06 mol of terephthalaldehyde and 0.3 mL of 5 mol / L acetic acid solution, continue stirring for 20 h, let stand for 2 h, centrifuge, wash, and dry to obtain a PNG / SnO2@COF composite material; Step S4, 3.5g of PNG / SnO2@COF composite material and 0.05g of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer were stirred in 60g of boiling deionized water for 30min, then transferred to an autoclave for reaction at 170°C for 10h, centrifuged and dried, and then placed in a tubular furnace for sintering at 290°C for 5h to obtain a graphite negative electrode material. Example 3
[0012] The graphite negative electrode material is prepared by the following steps: Step S1, 9 g of natural graphite and 0.08 g of ammonium sulfate are mixed and ground, and the ground product is transferred to a quartz crucible, heat treated at 1350° C. for 4 h under nitrogen, and cooled to room temperature to obtain porous graphite; Step S2, 2 g of tin tetrachloride was mixed and stirred in 50 mL of ethanol, 0.15 g of porous graphite was added, ultrasonicated for 5 h, stirred at a speed of 600 rpm for 19 h, centrifuged, washed, freeze-dried, and then calcined at 850 ° C for 3 h to obtain a PNG / SnO2 composite material; Step S3, ultrasonically disperse 1 g of PNG / SnO2 composite material in 100 mL of acetonitrile for 20 min, add 0.03 mol of melamine and stir for 1.5 h, then add 0.065 mol of terephthalaldehyde and 0.4 mL of 3.5 mol / L acetic acid solution, continue stirring for 22 h, let stand for 2.5 h, centrifuge, wash, and dry to obtain a PNG / SnO2@COF composite material; Step S4, 4 g of PNG / SnO2@COF composite material and 0.07 g of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer were stirred in 60 g of boiling deionized water for 30 min, then transferred to an autoclave for reaction at 180 ° C for 11 h, centrifuged and dried, and then placed in a tubular furnace for sintering at 290 ° C for 5 h to obtain a graphite negative electrode material. Example 4
[0013] The graphite negative electrode material is prepared by the following steps: Step S1, 10 g of natural graphite and 0.1 g of ammonium sulfate are mixed and ground, and the ground product is transferred to a quartz crucible, heat-treated at 1400° C. for 4 h under nitrogen, and cooled to room temperature to obtain porous graphite; Step S2, 3 g of tin tetrachloride was mixed and stirred in 50 mL of ethanol, 0.2 g of porous graphite was added, ultrasonicated for 5 h, stirred at a speed of 700 rpm for 20 h, centrifuged, washed, freeze-dried, and then calcined at 900 ° C for 3.5 h to obtain a PNG / SnO2 composite material; Step S3, ultrasonically disperse 1 g of PNG / SnO2 composite material in 100 mL of acetonitrile for 20 min, add 0.03 mol of melamine and stir for 1.5 h, then add 0.07 mol of terephthalaldehyde and 0.5 mL of 3 mol / L acetic acid solution, continue stirring for 24 h, let stand for 3 h, centrifuge, wash, and dry to obtain a PNG / SnO2@COF composite material; Step S4, 5g of PNG / SnO2@COF composite material and 0.09g of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer were stirred in 60g of boiling deionized water for 30min, then transferred to an autoclave for reaction at 180°C for 12h, centrifuged and dried, and then placed in a tubular furnace for sintering at 310°C for 5.5h to obtain a graphite negative electrode material.
[0014] Comparative Example 1 This comparative example is a negative electrode material, which is a natural graphite@COF composite material, and is specifically prepared by the following steps: 1 g of natural graphite was ultrasonically dispersed in 100 mL of acetonitrile for 20 min, 0.03 mol of melamine was added and stirred for 1.5 h, and then 0.07 mol of terephthalaldehyde and 0.5 mL of 3 mol / L acetic acid solution were added, stirring was continued for 24 h, and the mixture was allowed to stand for 3 h. The mixture was centrifuged, washed and dried to obtain a natural graphite@COF composite material.
[0015] Comparative Example 2 This comparative example is a negative electrode material, which is a natural graphite@COF@PFA composite material, and is specifically prepared by the following steps: Step S1, 1 g of natural graphite was ultrasonically dispersed in 100 mL of acetonitrile for 20 min, 0.03 mol of melamine was added and stirred for 1.5 h, 0.07 mol of terephthalaldehyde and 0.5 mL of 3 mol / L acetic acid solution were added, stirring was continued for 24 h, standing for 3 h, centrifuging, washing and drying to obtain a natural graphite@COF composite material; Step S2, 5 g of natural graphite @ COF composite material and 0.09 g of tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer were stirred in 60 g of boiling deionized water for 30 min, then transferred to an autoclave for reaction at 180 ° C for 12 h, centrifuged and dried, and then placed in a tubular furnace for sintering at 310 ° C for 5.5 h to obtain a natural graphite @ COF @ PFA composite material.
[0016] The graphite negative electrode materials prepared in Examples 1-4, the natural graphite@COF composite materials in Comparative Example 1, and the natural graphite@COF@PFA composite materials in Comparative Example 2 were used as negative electrode materials for lithium batteries, respectively, mixed with acetylene black and sodium alginate in a ratio of 7:2:1 to prepare slurry, and coated to prepare negative electrode sheets; NCM811, acetylene carbon black and binder PVDF were mixed evenly in a mass ratio of 80:12:8, and coated on aluminum foil to prepare positive electrode materials; the separator was celgard2400, The electrolyte was prepared by using 1 mol / L LiPF6 conductive salt and DMC:DEC:EC (wt%) = 1:1:1 solvent to prepare a lithium battery; the prepared lithium battery was tested for the discharge specific capacity at the first charge and discharge at a charge and discharge cut-off voltage of 0.01-1.5V and 0.1C, and then the capacity retention rate after 500 cycles was tested, and then the capacity remaining rate (%) was tested at discharge rates of 0.05C, 0.5C, 1C and 10C respectively. The test results are shown in Table 1; Table 1: Performance test results
[0017] It can be seen from the above table that the negative electrode material prepared by the present invention has excellent cycle stability and rate performance after performance testing, and therefore has good application prospects in negative electrode materials for lithium batteries.
[0018] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A process for preparing high-performance graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the following steps: Step S1, mixing and grinding natural graphite and ammonium sulfate, transferring the ground product into a quartz crucible, heat treating it under nitrogen and high temperature conditions for 3-4 hours, and cooling it to room temperature to obtain porous graphite; Step S2, mixing tin tetrachloride in ethanol and stirring evenly, adding porous graphite and ultrasonicating for 3-5 hours, stirring at a speed of 500-700 rpm for 15-20 hours, centrifuging, washing, freeze-drying, and then calcining at high temperature to obtain a PNG / SnO2 composite material; Step S3, ultrasonically dispersing the PNG / SnO2 composite material in acetonitrile for 10-20 minutes, adding melamine and stirring for 0.5-1.5 hours, then adding terephthalaldehyde and 3-6 mol / L acetic acid solution, continuously stirring for 18-24 hours, standing for 1-3 hours, centrifuging, washing, and drying to obtain the PNG / SnO2@COF composite material; Step S4, stirring the PNG / SnO2@COF composite material and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer in boiling deionized water for 30 minutes, then transferring to an autoclave to react for 8-12 hours, centrifuging and drying, and then sintering in a tubular furnace to obtain a graphite negative electrode material.
2. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: The temperature during the heat treatment in step S1 is 1200-1400°C.
3. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: In step S1, the mass ratio of natural graphite to ammonium sulfate is 5-10:0.03-0.
1.
4. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: In step S2, the usage ratio of tin tetrachloride, ethanol and porous graphite is 0.5-3g:50mL:0.05-0.2g.
5. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: The high temperature calcination in step S2 is performed at a temperature of 700-900° C. and for a time of 1.5-3.5 hours.
6. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: In step S3, the usage ratio of the PNG / SnO2 composite material, acetonitrile, melamine, terephthalaldehyde and acetic acid solution is 1 g: 100 mL: 0.02-0.03 mol: 0.05-0.07 mol: 0.2-0.5 mL.
7. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: In step S4, the mass ratio of PNG / SnO2@COF composite material, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer and deionized water is 3-5:0.03-0.09:
60.
8. A process for preparing a high performance graphite negative electrode material according to claim 1, characterized in that: In step S4, the reaction temperature in the autoclave is 160-180° C., the sintering temperature in the tubular furnace is 280-310° C., and the sintering time is 4.5-5.5 h.
Citation Information
Patent Citations
Composite negative pole material for lithium-ion battery and manufacturing method of negative pole material
CN103247787A
Modified graphite negative electrode material, preparation method thereof and battery containing modified graphite negative electrode material
CN111276674A
Natural graphite-based silicon-carbon composite negative electrode material and preparation method and application thereof
CN113161521A
Sulfur-nitrogen doped porous carbon-based lithium ion battery material
CN116435447A
Preparation method for high capacity lithium-ion battery negative electrode material
WO2017024720A1
